2008
DOI: 10.1002/jat.1322
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of zearalenone and α‐zearalenol toxicity on boar sperm DNA integrity

Abstract: This study aimed at investigating the in vitro effects of zearalenone (zen) and alpha-zearalenol (alpha-zen) on motility and nuclear chromatin integrity (NCI) of boar spermatozoa. Mycotoxins were tested, at levels ranging from 10 to 30 microg ml(-1) of diluted semen. Four boars were used for semen collection (eight replicates per boar, four per mycotoxin). After the addition of zen or alpha-zen, semen samples were incubated for 4 h at 38.5 degrees C, 5% CO(2) and 96% humidified air. Motility and NCI were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 48 publications
(43 reference statements)
3
23
0
1
Order By: Relevance
“…Final concentrations in the samples tested were as follows: (1) E 2 , 10 μg/mL; (2) ginseng extract, 2 mg/mL; and (3) α-zearalenol, 10 μg/mL [53]. Extracts of ginseng were prepared by adding 10 mL 80% methanol to 2 g powdered root samples and shaking for 5 h. Samples were centrifuged at 1,800 g for 15 min and the supernatants removed.…”
Section: Methodsmentioning
confidence: 99%
“…Final concentrations in the samples tested were as follows: (1) E 2 , 10 μg/mL; (2) ginseng extract, 2 mg/mL; and (3) α-zearalenol, 10 μg/mL [53]. Extracts of ginseng were prepared by adding 10 mL 80% methanol to 2 g powdered root samples and shaking for 5 h. Samples were centrifuged at 1,800 g for 15 min and the supernatants removed.…”
Section: Methodsmentioning
confidence: 99%
“…Acute and chronic injection of ZEN, ␣-ZOL and ␤-ZOL by animals can elicit a variety of toxic effects, i.e. enlargement of mammary glands and uterus, infertility, vaginal prolapse and atrophy of testicles and ovaries [1,[3][4][5]. ␣-Zearalanol (␣-ZAL) is a resorcyclic acid lactone and might arise from the metabolism of ␣-ZOL or ZEN [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Tsakmakidis et al (2006) showed that exposure to ZEA led to a reduction in sperm viability, progressive motility and the percentage of sperm capable to undergo acrosome reaction. Moreover, in 2008, the same group revealed that ZEA also affected sperm chromatin integrity (Tsakmakidis et al 2008). Contrarily to boar, horse sperm was thought to be less susceptible to the effects of ZEA.…”
Section: Phytoestrogens and Mycotoxinsmentioning
confidence: 99%